Health and economic benefits of physical activity for patients with spinal cord injury - Miller LE; Herbert WG (Dove Medical Press, 2016)
Larry E Miller,1 William G Herbert1,2 1Miller Scientific Consulting, Inc., Asheville, NC, 2Department of Human Nutrition, Foods & Exercise, Virginia Tech, Blacksburg, VA, USA Abstract: Spinal cord injury (SCI) is a traumatic, life-disrupting event with an annual incidence of 17,000 cases in the US. SCI is characterized by progressive physical deconditioning due to limited mobility and lack of modalities to allow safe physical activity that may partially offset these deleterious physical changes. Approximately, 50% of patients with SCI report no leisure-time physical activity and 15% report leisure-time physical activity below the threshold where meaningful health benefits could be realized. Collectively, about 363,000 patients with SCI, or 65% of the entire spinal cord injured population in the US, engages in insufficient physical activity and represents a target population that could derive considerable health benefits from even modest physical activity levels. Currently, the annual direct costs related to SCI exceed US$45 billion in the US. Rehabilitation protocols and technologies aimed to improve functional mobility have potential to significantly reduce the risk of medical complications and cost associated with SCI. Patients who commence routine physical activity in the first post-injury year and experience typical motor function improvements would realize US$290,000 to US$435,000 in lifetime cost savings, primarily due to fewer hospitalizations and less reliance on assistive care. New assistive technologies that allow patients with SCI to safely engage in routine physical activity are desperately needed. Keywords: ambulation, cost, exercise, exoskeleton, paraplegia, physical activity, spinal cord injury